The concordance of preoperative digital cephalometric simulation with postoperative outcomes in orthognathic surgery patients - Odeh, Noura Jamil Hussein (My University, 2021)
AIM: To compare computerized orthognathic predictions produced by NemoCephsoftware with the actual outcomes in orthognathic surgery patients.MATERIAL and METHOD: We used postoperative cephalometric radiographs of 30 orthognathic surgery patients, obtained 1-4 months after surgery, that were traced using NemoCeph orthodontic software, the measurements were compared to the predicted measurements preoperative measures. The parameters used were SNA angle, SNB angle, SN-Go-Me angle, SN-PP angle, ANS-Me/ N-Me ratio and Ar-Go/ N-Me ratio. Bland & Altman test was used to evaluate the agreement between the simulated measurements and the actual postoperative measurements .RESULTS: The mean differences (x) and their standard deviations(SD) between the predicted and actual measurements were as follows: SNA: x= 0.766 , SD=3.6, SNB: x=0.6667, SD=2.22, SN-Go-Me: x=0.9333, SD=3.96, Sn-PP: x=1.267, SD=2.74, ANS-Me/ N-Me: x=0.3733 SD=2.21, Ar-Go/ N-Me: x=0.89, SD=3.92 . Except for Ar- Go/ N-Me ratio and Sn-PP, the differences between the two measurements in all parameters were distributed within two standard deviations below and above the mean with SNA , Ar-Go/ N-Me , and ANS-Me/ N-Me each had one outlier, SNB had no outlier, SN-Go-Me and SN-PP each had three outliers .CONCLUSION: The predicted preoperative cephalometric measurements generated using NemoCeph orthodontic software showed acceptable concordance with the actual postoperative outcomes in surgically treated orthognathic patients. Concordance in sagittal measurements was higher compared to vertical ones.

AMAÇ: NemoCeph ortodontik yazılımı tarafından üretilen bilgisayarlı ortognatiktahminleri cerrahi olarak tedavi edilen ortodontik hastalarda gerçek tedavi sonuçlarıyla karşılaştırmaktır.GEREÇ VE YÖNTEMLER: 30 ortognatik cerrahi hastasının ameliyattan 1-4 ay sonra elde edilen postoperatif sefalometrik radyografileri NemoCeph ortodontik yazılımı kullanılarak çizilmiş ve preoperatif olarak üretilen simülasyon ölçümleriyle karşılaştırılmıştır. Kullanılan parametreler SNA açısı, SNB açısı, SN-Go-Me açısı, SN-PP açısı, ANS-Me / N-Me oranı ve Ar-Go / N-Me oranıydı. Tahmin edilen ölçümler ile gerçek postoperatif ölçümler arasındaki uyumu değerlendirmek için Bland & Altman plot analizi yapılmıştır.BULGULAR: Tahmini ve gerçek ölçümler arasındaki ortalama farklar (x) ve bunların standart sapmaları (SD) aşağıdaki gibidir: SNA: x= 0.766 , SD=3.6, SNB: x=0.6667, SD=2.22, SN-Go-Me: x =0.9333, SD=3.96, Sn-PP: x=1.267, SD=2.74, ANS-Me/ N- Me: x=0.3733 SD=2.21, Ar-Go/ N-Me: x=0.89, SD=3.92. Ar-Go/ N-Me oranı ve Sn- PP hariç, tüm parametrelerde iki ölçüm arasındaki farklar, SNA, Ar-Go/ N-Me ve ANS-Me içi ortalamanın altında ve üstünde iki standart sapma içinde dağımıştır. SNA, Ar-Go/ N-Me , ve ANS-Me/ N-Me her birinin bir aykırı değeri, SN-Go-Me'nin üç aykırı değeri ve SN-PP'nin üç aykırı değeri varder, SNB'nin hiç değeri yoktu. SONUÇ: NemoCeph ortodontik yazılımı kullanılarak oluşturulan tahmini preoperatif sefalometrik ölçümler, cerrahi olarak tedavi edilen ortognatik hastalarda gerçek postoperatif sonuçlarla kabul edilebilir bir uyum göstermıştır. Sagital ölçümlerde uyum dikey olanlara göre daha yüksektir.
Keywords: Cephalometric Simulation; Digital orthodontic Ortognatik Cerrahi; Dijital ortodonti; Orthodontics; Orthognathic surgery; Ortodonti; Sefalometrik Simülasyon